2011
DOI: 10.1017/s0025315411001482
|View full text |Cite
|
Sign up to set email alerts
|

Benthic macrofauna associated with decomposition of leaves in a mangrove forest in Ilhéus, State of Bahia, Brazil

Abstract: We identified and quantified the benthic macrofauna associated with decomposing leaves of Rhizophora mangle and Laguncularia racemosa, to observe the differences in the abundance and composition of macrofauna between these mangrove species, and to examine whether the abundance and composition of organisms changed with different stations and collection times. Benthic macrofauna, mainly polychaetes and amphipods, were recorded from the fifth day after the installation of the experiment. Annelids including Oligoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Nordhaus et al (2011) suggested that plants with larger amounts of nitrogenous compounds were the preferred food for mangrove crabs. They feed on microorganisms, sediments and organic matter that settle on the leaf surface (Oliveira et al, 2012). Most annelid species in estuarine areas are surface deposit-feeders, with discrete motility and opportunistic behaviours (Magalhães & Barros, 2011;Oliveira et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nordhaus et al (2011) suggested that plants with larger amounts of nitrogenous compounds were the preferred food for mangrove crabs. They feed on microorganisms, sediments and organic matter that settle on the leaf surface (Oliveira et al, 2012). Most annelid species in estuarine areas are surface deposit-feeders, with discrete motility and opportunistic behaviours (Magalhães & Barros, 2011;Oliveira et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The low N content and the thick cuticle of R. mangle may repel the crabs, but also these features may attract the annelids that were the predominant invertebrate group in this mangrove species. The different abundances of decapods and annelids on the three mangrove species and their respective decomposition rates may also suggest that annelids are less efficient shredders than decapods, although Camilleri (1992) and Oliveira et al (2012) noted the important role of polychaetes in processing leaves in tropical mangroves. They feed on microorganisms, sediments and organic matter that settle on the leaf surface (Oliveira et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations